Bayesian Deep Learning : work with Bayesian neural networks BNN and BDL to employ an ensemble of deep learning models /: work with Bayesian neural networks BNN and BDL to employ an ensemble of deep learning models. (2023) - Benatan, Matt; Gietema, Jochem; Schneider, Marian
No abstract available